Modulating interoception by insula stimulation: A double-blinded tDCS study. (23rd March 2019) - Sagliano, Laura; Magliacano, Alfonso; Parazzini, Marta; Fiocchi, Serena; Trojano, Luigi; Grossi, Dario
Highlights: Interoceptive accuracy can be improved by task repetition. Insula stimulation reduced practice effect in interoceptive accuracy. It is possible to modulate interoception by stimulating insula via a tDCS protocol. Abstract: Interoception consists in the perception and processing of internal body signals, such as heartbeat. Previous neuroimaging studies revealed that attention to heartbeat activated bilateral insula and premotor regions. In the present double-blind study, we aimed at testing the role of insula in interoception by means of transcranial direct current stimulation (tDCS) interfering with its activity. Sixteen healthy participants responded to a questionnaire to evaluate the tendency to be internally focused and performed a heartbeat counting task before and after tDCS in three sessions (left insula stimulation, right insula stimulation, sham stimulation). Real and reported heartbeat were recorded and used to calculate the accuracy scores. A significant interaction between stimulation condition and time (pre- and post-stimulation) was found due to a significant improvement of the interoceptive accuracy in the sham condition only. Our results demonstrated that stimulation over the insula reduced the possibility to improve the precision with which individuals detect internal signals.